2019
DOI: 10.1039/c9lc00649d
|View full text |Cite
|
Sign up to set email alerts
|

Building a microfluidic cell culture platform with stiffness control using Loctite 3525 glue

Abstract: The study of cell response to mechanotransduction signals requires designing culture substrates offering biocompatibility and adhesion, stiffness control and dynamics, patternability at microscale and integration in microfluidics chips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…It was recently reported that mouse primary hepatocytes respond to stiff PAA hydrogels (with an elastic modulus ≥10 kPa) by doubling their area in the first 12 h after seeding; however, this effect seems to be attenuated in viscoelastic PAA HGs [26,37]. To evaluate our conditions and confirm previous results, we decided to use soft (1 kPa, elastic modulus) and stiff (20 kPa, elastic modulus) polyacrylamide hydrogels conjugated with rat tail collagen type I as described in [74]. We evaluated the spreading of primary hepatocytes at 24 and 72 h after culture (Figure 1A).…”
Section: Stiffness Promotes Cell Aggregation and Triggers Spreading In Primary Hepatocytes Whereas Collagen Type I Promotes Cell Adhesionmentioning
confidence: 60%
See 1 more Smart Citation
“…It was recently reported that mouse primary hepatocytes respond to stiff PAA hydrogels (with an elastic modulus ≥10 kPa) by doubling their area in the first 12 h after seeding; however, this effect seems to be attenuated in viscoelastic PAA HGs [26,37]. To evaluate our conditions and confirm previous results, we decided to use soft (1 kPa, elastic modulus) and stiff (20 kPa, elastic modulus) polyacrylamide hydrogels conjugated with rat tail collagen type I as described in [74]. We evaluated the spreading of primary hepatocytes at 24 and 72 h after culture (Figure 1A).…”
Section: Stiffness Promotes Cell Aggregation and Triggers Spreading In Primary Hepatocytes Whereas Collagen Type I Promotes Cell Adhesionmentioning
confidence: 60%
“…Immunofluorescence and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assays were performed in rat primary hepatocytes cultured on PAA HGs as described in [74]. Briefly, hepatocytes were washed once with pre-warmed 1× DPBS and immediately fixed with 4% paraformaldehyde (PFA) in DPBS 1× at 37 • C for 20 min.…”
Section: Immunofluorescence and Tunel Assaymentioning
confidence: 99%
“…When the determination of Young's modulus of a material is required, for instance for quantifying the influence of substrate mechanics on cell spreading [62,63] or determining forces reliably using traction force microscopy measurements [64], our method also readily enables its determination from the relaxation data and GMM analysis. For that, we compared the calculated values of the elastic modulus obtained with conventional microindentation and with the relaxation tests.…”
Section: Comparison Between Microindentation and Relaxation Mechanicamentioning
confidence: 99%
“…Part Ba adapted with permission from ref. 77 substrates in the OoC device, whereby the stiffness 190,191 or surface topographies 192,193 of the substrates can be precisely controlled.…”
Section: Probing and Mimicking The Cell Microenvironmentmentioning
confidence: 99%